16. Experimental animal research on the subchronic toxicity of “Dứa Tre Lão Nhà Quê” extract - Anh, Pham Thi Van; Hang, Vu Viet; Thuy, Nguyen Thi; Duong, Dau Thuy (Tạp chí Nghiên cứu Y học, 2024)
“Dứa tre Lão nhà quê” extract (DTLNQ extract) was intended to treat several diseases such as dyslipidemia and venous insufficiency. To provide information on the its safety, this study evaluated the subchronic toxicity of DTLNQ extract. Wistar rats were divided into three groups and were given orally for 12 weeks: group 1 distilled water; group 2 and group 3: DTLNQ extract at 0.6g and 1.8g/kg b.w./day, respectively. General conditions and body weight change, hematological and biochemical parameters, and hepatic and renal histological examinations were evaluated in treated rats compared with the control group and baseline. The results showed that DTLNQ extract did not cause significant changes in general conditions, body weight gain, hematological parameters, biochemical parameters of hepatic and renal function tests and the histological examination of the liver and kidneys. Though the values of AST and ALT increased after 12 weeks of administration compared with the control group and baseline, they were within the normal limits or slightly greater than the upper limit of normal in rats.